Construct validity of the Modified Gait Efficacy Scale in older females. (18th May 2016) - Goldberg, Allon; Talley, Susan Ann; Adamo, Diane E.
ABSTRACT: There are few well-validated tools that focus on the assessment of walking confidence in older adults. The main objective of this study was to assess construct validity of the 10-item Modified Gait Efficacy Scale (mGES) as a measure of walking confidence in older adults. Twenty-four older females completed the mGES, the 16-item Activities-specific Balance Confidence (ABC-16) scale, and the Senior Fitness Test (SFT). Construct validity of the mGES was evaluated by quantifying relationships between the mGES and the ABC-16 and the SFT, and by examining the ability of the mGES to discriminate between known groups (no/lower fear of falling versus higher fear of falling). There was a strong correlation between mGES and the ABC-16 scale ( rs = 0.85; p < 0.001). The mGES was significantly associated with SFT components that required lower extremity strength, stepping aerobic endurance, and walking agility and dynamic balance ( rs = 0.45 to 0.61; p < 0.05). Relationships between the mGES and number of arm curls in 30 s, chair sit and reach test, and back scratch test were weak ( rs = 0.13–0.25; p > 0.05). Mean mGES score was 91.5% in a no/lower fear of falling group, while it was 81.4% in a higher fear group ( p = 0.22). There was a trend toward a significant difference in the unstandardized residuals derived from regression of ranked mGES scores on ranked covariate (age and 8 foot up and go) scores, between the no/lower versus higher fear of falling group ( p = 0.095). These results support construct validity of the mGES as a measure of gait self-efficacy in community-dwelling older females.